Wurtzite (Ga, Mn)As nanowire shells with ferromagnetic properties. Issue 6 (25th January 2017) - Sadowski, J.; Kret, S.; Šiušys, A.; Wojciechowski, T.; Gas, K.; Islam, M. F.; Canali, C. M.; Sawicki, M.
Abstract : (Ga, Mn)As having a wurtzite crystal structure was coherently grown by molecular beam epitaxy on the 1100 side facets of wurtzite (Ga, In)As nanowires and further encapsulated by (Ga, Al)As and low temperature GaAs. Only in this kind of core–multishell nanowire heterostructures the long range ferromagnetic order in (Ga, Mn)As NW shells has been observed. Abstract : (Ga, Mn)As having a wurtzite crystal structure was coherently grown by molecular beam epitaxy on the 1100 side facets of wurtzite (Ga, In)As nanowires and further encapsulated by (Ga, Al)As and low temperature GaAs. For the first time, a truly long-range ferromagnetic magnetic order is observed in non-planar (Ga, Mn)As, which is attributed to a more effective hole confinement in the shell containing Mn by the proper selection/choice of both the core and outer shell materials.